1960
DOI: 10.2134/agronj1960.00021962005200070009x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Mineral Content of Corn as Affected by Ammonium Chloride Fertilizer1

Abstract: Synopsis Yield of corn fertilized with NH4Cl was not significantly different from corn fertilized with other common nitrogen carriers. Increased absorption of Cl by plants did not alter the plant content of other mineral elements. Spring‐applied Cl was largely leached from the soil by the following spring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1976
1976
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Increases in grain yield were associated with linear increases in ear size, which were significant at P = 0.04, 0.09, and 0.07 in 1990, 1991, and 1992, respectively. Yield levels were twoto three-fold higher in this experiment than in previous studies that did not obtain yield increases from Cl fertilization of corn (Younts and Musgrave, 1958a;Teater et al, 1960;Parker et al, 1985;Schumacher and Fixen, 1989). Hybrid effects may also be a contributing factor to variation in corn responses to Cl as with wheat cultivars (Engel and Sanders, 1992).…”
Section: Results and Discussion Grain And Stover Yield Responsecontrasting
confidence: 43%
See 2 more Smart Citations
“…Increases in grain yield were associated with linear increases in ear size, which were significant at P = 0.04, 0.09, and 0.07 in 1990, 1991, and 1992, respectively. Yield levels were twoto three-fold higher in this experiment than in previous studies that did not obtain yield increases from Cl fertilization of corn (Younts and Musgrave, 1958a;Teater et al, 1960;Parker et al, 1985;Schumacher and Fixen, 1989). Hybrid effects may also be a contributing factor to variation in corn responses to Cl as with wheat cultivars (Engel and Sanders, 1992).…”
Section: Results and Discussion Grain And Stover Yield Responsecontrasting
confidence: 43%
“…Generally, they were not mfluenced by Cl rate (Table 4). Previous studies (Parker et al, 1985;Teater et al, 1960;Younts and Musgrave 1958a) also found no influence of Cl fertilization on the concentration of other elements in the ear-leaf. Although increasing rates of Cl application were accompanied by decreasing rates of OH-and soa-application, ear-leaf analysis did not indicate an influence of OH-and Soa-rate on plant nutrient status.…”
Section: Plant Nutrient Compositionmentioning
confidence: 78%
See 1 more Smart Citation
“…From these results it is concluded that the breakdown •Jf the stalk tissue which led to lodging was due to low potassium, since the addition of chloride as ammo:1ium chloride did not reduce the lodging. Chloride from the NH 4 Cl, while not measured directly by plant analysis, should have been readily taken up (8) and should have reduced lodging if chloride had been :~esponsible for reduced lodging. In previous years on this experimental site, lodging on the NP treatments was as high as 78%, whereas on those receiving NPK with potassium as KCl, it was 10% or less.…”
Section: Resultsmentioning
confidence: 99%